Investigating the relationship between personality types and the age of first pregnancy in women referring to hospitals affiliated to Shiraz University of Medical Sciences - Sahar Parvizi; Marzieh Akbarzadeh (Armaghane Danesh Bimonthly Journal, 2023)
Abstract Introduction and goal Personality traits are effective in human decision-making, and researchers try to investigate the role of personality in personal choices , and deciding when to get pregnant in women is one of these choices. The purpose of this research is to identify the relationship between the personality characteristics of pregnant women and the age of the first pregnancy. materials and methods This research is a descriptive-analytical cross-sectional study that was conducted on 210 eligible mothers by random sampling method from three centers. Personality questionnaire and personal information questionnaire were completed by mothers. Data analysis was done by Pearson and Spearman statistical tests and using SPSS software. findings The results showed that the correlation value of two variables, extroversion and age of first pregnancy, with a correlation of 0.17 with a significance level of 0.014, and openness to experience and age of the first pregnancy with a correlation of 0.25 with a significance level of 0.049, which is from the assumed error in the research. , are less than 0.05, it is significant. Conclusion According to the results of this research and the relationship between personality traits and the age of the first pregnancy, recognizing personality types of women and provide training and counseling to improve personality traits in order to reduce the fertility rate and complications of pregnancy in old age, is suggested.